The Impact of Atmosphere on the Local Luminescence Properties of Metal Halide Perovskite Grains. Issue 15 (7th March 2018) - Brenes, Roberto; Eames, Christopher; Bulović, Vladimir; Islam, M. Saiful; Stranks, Samuel D.
Abstract: Metal halide perovskites are exceptional candidates for inexpensive yet high‐performing optoelectronic devices. Nevertheless, polycrystalline perovskite films are still limited by nonradiative losses due to charge carrier trap states that can be affected by illumination. Here, in situ microphotoluminescence measurements are used to elucidate the impact of light‐soaking individual methylammonium lead iodide grains in high‐quality polycrystalline films while immersing them with different atmospheric environments. It is shown that emission from each grain depends sensitively on both the environment and the nature of the specific grain, i.e., whether it shows good (bright grain) or poor (dark grain) luminescence properties. It is found that the dark grains show substantial rises in emission, while the bright grain emission is steady when illuminated in the presence of oxygen and/or water molecules. The results are explained using density functional theory calculations, which reveal strong adsorption energies of the molecules to the perovskite surfaces. It is also found that oxygen molecules bind particularly strongly to surface iodide vacancies which, in the presence of photoexcited electrons, lead to efficient passivation of the carrier trap states that arise from these vacancies. The work reveals a unique insight into the nature of nonradiative decay and the impact of atmospheric passivation on the microscale properties of perovskite films. Abstract : Metal halide perovskites are an exciting class of materials for low‐cost optoelectronics but their performance remains limited by nonradiative losses. The surface adsorption of different atmospheric molecules to different types of grains in perovskite films can have a profound impact on the local luminescence of that grain under continual illumination depending on whether the grain has few (bright grain) or many (dark grain) defects. Oxygen molecules are shown to bind particularly strongly to iodide vacancies which, in the presence of photoexcited electrons, leads to passivation of the carrier trap states that arise from these vacancies.